AN IMPROVED METHOD FOR EXTRACTION OF HETEROLOGOUS DNA FROM ENVIRONMENTAL SAMPLES FOR THE CONSTRUCTION OF METAGENOMIC LIBRARIES - DR. PINDI PAVAN KUMAR (International Journal of Pharma and Bio Sciences, 2011)
Soil represents a diverse group of microorganism, which has frequently been used to isolate and explore and exploit microbes for industrial, environmental and agriculture applications. Presently, several methods are being used to isolate the DNA from environmental samples. This paper deals with an improved method developed for the isolation of heterologous DNA from environmental soils or sediments. This approach consists of the direct extraction of large fragmented nucleic acids from soil followed by purification. Cell lysis is a critical step in soil metagenomic DNA extraction. Extraction procedure was optimized with series of steps, which involved gentle mechanical lysis and number of freeze-thawing cycles in liquid nitrogen and with variations in incubation period and temperature. A comparison of the optimized protocol with other existing protocols and with commercially available kit suggests that protocol described in this report would be more efficient and yields high quantity and quality DNA from environmental samples.